Research for a new world: Critical thinking for the water–energy–food–ecosystems nexus (work packages) - McCartney, Matthew P.; Ringler, Claudia (CGIAR System Organization, 2022)
Together, climate change, environmental degradation and biodiversity loss represent the largest existential threat to humanity. That much was clear as we participated in both the United Nations Framework Convention on Climate Change (UNFCCC) 27th session of the Conference of the Parties (COP27) and the Ramsar Convention on Wetlands' COP14 in November, and now look ahead to the upcoming biodiversity COP15. With nine interventions at COP27 alone, we are committed to being part of the increasingly convergent global discourse on climate change, water, energy, food and ecosystem health.